A PC-PMMA composite protective film and preparation method thereof

By adding anti-rushing agents and nanoparticles to the PC-PMMA composite film, and using a double-layer composite crowding process, the problem of poor interface binding strength is used to improve the impact strength and wear resistance of the composite membrane. Improve its application performance.

CN118438765BActive Publication Date: 2025-01-24HEYUAN KUNTENG ELECTRONIC TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410250100.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-05
Publication Date
2025-01-24
Estimated Expiration
2044-03-05

AI Technical Summary

Technical Problem

In applications, PC-PMMA composite membrane has the problem of poor bonding strength between PC and PMMA interfaces, which affects its mechanical properties and limits its application in the field of mobile phone back cover manufacturing.

Method used

By adding anti-flushing agents and antioxidants to PMMA resin, nanoparticles are added to the PC resin, and a double-layer composite crowding process is used to form a PC-PMMA composite protective film to enhance its impact strength and abrasion resistance.

Benefits of technology

The abrasion resistance and toughness of the PC-PMMA composite protective film is improved, its impact strength is enhanced, and its application performance in the field of manufacturing in the back cover of the mobile phone is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004727290250000061
    Figure BDA0004727290250000061
  • Figure BDA0004727290250000071
    Figure BDA0004727290250000071
  • Figure BDA0004727290250000081
    Figure BDA0004727290250000081
Patent Text Reader

Abstract

The present application relates to the technical field of composite materials, and specifically discloses a PC-PMMA composite protective film and a preparation method thereof. A PC-PMMA composite protective film comprises a PMMA layer and a PC layer; the PMMA layer comprises the following components: PMMA resin, an impact modifier and an antioxidant; the PC layer comprises the following components: PC resin and nanoparticles. The preparation method of the PC-PMMA composite protective film comprises the following steps: S1, preparing PMMA particles and PC particles; S2, melt-extrude the PMMA particles to obtain a PMMA melt; melt-extrude the PC particles to obtain a PC melt; S3, distribute the PMMA melt and the PC melt to a die head for double-layer composite co-extrusion, plasticization, calendering, traction cooling and shaping, to obtain a PC-PMMA composite protective film. The PC-PMMA composite protective film prepared in the present application has good wear resistance and toughness, and high impact strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a PC-PMMA composite protective film and a preparation method thereof. Background Art

[0002] With the continuous development of communication technology, the design of future 5G mobile phones using millimeter wave communication and 5G antennas will place increasingly stringent requirements on mobile phone case materials, and the trend of demetallization of mobile phone back shells will accelerate.

[0003] The back cover made of PC-PMMA composite film has good mechanical properties due to its co-extruded double-layer structure and has been widely used in the field of mobile phone back cover manufacturing. Polycarbonate has high light transmittance and impact strength, but poor wear resistance; polymethyl methacrylate has good wear resistance and excellent optical properties, but low impact strength. Although the two can be combined to maximize their strengths and minimize their weaknesses, there is still the problem of poor interface bonding strength between PC and PMMA, which affects the overall mechanical properties of the prepared PC-PMMA composite film and limits the application of PC-PMMA composite film. Summary of the invention

[0004] In order to solve at least one of the above technical problems and develop a composite film with good mechanical properties, the present application provides a PC-PMMA composite protective film.

[0005] On the one hand, the present application provides a PC-PMMA composite protective film, comprising a PMMA layer and a PC layer;

[0006] The PMMA layer comprises the following components: PMMA resin, impact modifier and antioxidant, wherein the weight ratio of the PMMA resin, impact modifier and antioxidant is (70-85): (5-13): (0.1-0.4);

[0007] The impact modifier comprises the following components in parts by weight: 15-20 parts of n-butyl acrylate, 15-20 parts of methyl methacrylate, 5-8 parts of styrene, 0.8-1.2 parts of initiator, 0.5-1 parts of grafting agent, 0.5-1 parts of crosslinking agent, 1-2 parts of emulsifier, 0.1-0.3 parts of magnesium sulfate and 70-80 parts of water;

[0008] The PC layer comprises the following components: PC resin and nanoparticles, and the weight ratio of the PC resin to the nanoparticles is (20-30): (2-4).

[0009] By adopting the above technical scheme, the present application adds an impact modifier and an antioxidant to the PMMA resin, the impact modifier can enhance the impact strength of the PMMA layer, and the antioxidant makes the PMMA layer less susceptible to thermal oxidative aging and decomposition during processing and use; adding nanoparticles to the PC resin can effectively improve the wear resistance of the PC layer, and can also increase the interface area of ​​PC / PMMA, thereby enhancing the interaction between the two and improving the toughness of the PC-PMMA composite protective film; the present application prepares the PC-PMMA composite protective film by composite co-extrusion of the PMMA layer and the PC layer, which has good wear resistance and toughness and high impact strength.

[0010] Optionally, the impact modifier is prepared by the following method: mixing an emulsifier and water and heating to 75-78° C., adding n-butyl acrylate, styrene, a grafting agent and a cross-linking agent, stirring and mixing, then adding an initiator and methyl methacrylate, stirring and mixing, then adding magnesium sulfate, and then filtering and drying to obtain the impact modifier.

[0011] By adopting the above technical scheme, the present application adopts a seed emulsion polymerization method to prepare a core-shell structure impact modifier with polybutyl acrylate and styrene as the core and polymethyl methacrylate as the shell. The core-shell structure impact modifier has good compatibility with PMMA resin, has a good toughening effect, and the formed PMMA layer has high impact strength.

[0012] Optionally, the antioxidant is the antioxidant DLTP.

[0013] Optionally, the nanoparticles are modified nanoparticles, and the modified nanoparticles include one or both of modified nano-silicon dioxide and modified nano-zirconium dioxide.

[0014] Optionally, the preparation method of the modified nanoparticles is as follows: unmodified nanoparticles are dispersed in deionized water, tris(hydroxymethyl)aminomethane is added, and finally dopamine hydrochloride is added, and the mixture is stirred for reaction for 3-4 hours, filtered, washed with deionized water, and then dried to obtain modified nanoparticles.

[0015] Optionally, the weight ratio of the unmodified nanoparticles, tris(hydroxymethyl)aminomethane and dopamine hydrochloride is (2-4): (1-2): (0.3-0.5)

[0016] By adopting the above technical scheme, the present application modifies a layer of polydopamine on the surface of nano-silicon dioxide and nano-zirconium dioxide. The surface functionalization of polydopamine improves the dispersibility of nano-silicon dioxide and nano-zirconium dioxide in PC resin, strengthens the bonding strength of nano-silicon dioxide, nano-zirconium dioxide and PC resin, and can effectively improve the wear resistance and scratch resistance of the PC layer; at the same time, polydopamine is an adhesive biological adhesive. When nano-silicon dioxide and nano-zirconium dioxide with surface modified with polydopamine are introduced into the PC layer, the adhesion between the PC layer and the PMMA layer can be enhanced through the adhesion of polydopamine, thereby enhancing the interaction between them, and then improving the toughness of the PC-PMMA composite protective film.

[0017] Optionally, the modified nanoparticles are modified nano-silicon dioxide and modified nano-zirconium dioxide, and the weight ratio of the modified nano-silicon dioxide to the modified nano-zirconium dioxide is (2-4):1.

[0018] Optionally, the thickness ratio of the PMMA layer to the PC layer is 1:(12-16), and the thickness of the PC-PMMA composite protective film is 450-600 μm.

[0019] By adopting the above technical solution, the present application limits the thickness ratio of the PMMA layer to the PC layer to 1:(12-16), and the coordination of the various parts of the PC-PMMA composite protective film is higher; the thickness of the PC-PMMA composite protective film is within the above thickness range. When the PC / PMMA composite sheet is used in the field of mobile phone and tablet manufacturing, the mobile phone casing is easier to dissipate heat, which helps to improve the stability of the PC-PMMA composite protective film.

[0020] In a second aspect, the present application provides a method for preparing the above-mentioned PC-PMMA composite protective film, comprising the following steps:

[0021] S1, taking PMMA resin, impact modifier and antioxidant to prepare PMMA particles, taking PC resin and nanoparticles to prepare PC particles;

[0022] S2, melting the PMMA particles, and extruding at 245-255° C. to obtain a PMMA melt; melting the PC particles, and extruding at 260-270° C. to obtain a PC melt;

[0023] S3, distributing the PMMA melt and the PC melt into a die head for double-layer composite co-extrusion, plasticization, calendering, pulling, cooling and shaping, to obtain a PC-PMMA composite protective film.

[0024] By adopting the above technical scheme, the present application realizes the formation and mutual connection of PC layer and PMMA layer by co-extrusion after PC melt and PMMA melt are separated into runners, and utilizes the high temperature during co-extrusion to improve the interfacial adhesion between PC layer and PMMA layer, thereby obtaining better mechanical properties, and the obtained PC-PMMA composite protective film has better comprehensive performance.

[0025] Optionally, the preparation method of the PMMA particles is: uniformly mix PMMA resin, impact modifier and antioxidant to form a first mixture; blend and extrude the first mixture into granules at an extrusion temperature of 210 to 230° C.; and dry the extruded particles at 75 to 85° C. for 3 to 5 hours to obtain the PMMA particles.

[0026] Optionally, the preparation method of the PC particles is: mixing PC resin and nanoparticles uniformly to form a second mixture; blending and extruding the second mixture into granules at an extrusion temperature of 250 to 270° C.; and drying the extruded particles at 110 to 130° C. for 3.5 to 5 hours to obtain the PC particles.

[0027] In summary, the present invention includes at least one of the following beneficial technical effects:

[0028] 1. The present application adds an impact modifier and an antioxidant to the PMMA resin. The impact modifier can enhance the impact strength of the PMMA layer, and the antioxidant makes the PMMA layer less susceptible to thermal oxidative aging and decomposition during processing and use. The addition of nanoparticles to the PC resin can effectively improve the wear resistance of the PC layer and increase the interface area of ​​PC / PMMA, thereby enhancing the interaction between the two and improving the toughness of the PC-PMMA composite protective film. The present application prepares a PC-PMMA composite protective film by co-extruding the PMMA layer and the PC layer, which has good wear resistance and toughness and high impact strength.

[0029] 2. The present application adopts a seed emulsion polymerization method to prepare a core-shell structure impact modifier with polybutyl acrylate and styrene as the core and polymethyl methacrylate as the shell. The core-shell structure impact modifier has good compatibility with PMMA resin and has a good toughening effect. The formed PMMA layer has high impact strength. The present application modifies the surface of nano-silicon dioxide and nano-zirconium dioxide with a layer of polydopamine. The surface functionalization of polydopamine improves the dispersibility of nano-silicon dioxide and nano-zirconium dioxide in PC resin, strengthens the bonding strength of nano-silicon dioxide, nano-zirconium dioxide and PC resin, and can effectively improve the wear resistance and scratch resistance of the PC layer. At the same time, polydopamine is an adhesive biological adhesive. When nano-silicon dioxide and nano-zirconium dioxide with surface modified with polydopamine are introduced into the PC layer, the adhesion between the PC layer and the PMMA layer can be enhanced through the adhesion of polydopamine, thereby enhancing the interaction between them, and then improving the toughness of the PC-PMMA composite protective film.

[0030] 3. The present application defines the thickness ratio of the PMMA layer to the PC layer as 1:(12-16), and the various parts of the PC-PMMA composite protective film are more coordinated; the thickness of the PC-PMMA composite protective film is within the above thickness range. When the PC / PMMA composite sheet is used in the field of mobile phone and tablet manufacturing, the mobile phone casing is easier to dissipate heat, which helps to improve the stability of the PC-PMMA composite protective film.

[0031] 4. The present application realizes the formation and interconnection of PC layer and PMMA layer by co-extrusion after PC melt and PMMA melt are separated into runners, and utilizes the high temperature during co-extrusion to improve the interfacial adhesion between PC layer and PMMA layer, thereby obtaining better mechanical properties, and the obtained PC-PMMA composite protective film has better comprehensive performance. DETAILED DESCRIPTION

[0032] The present application is further described in detail below with reference to the embodiments.

[0033] The present application designs a PC-PMMA composite protective film, comprising a PMMA layer and a PC layer;

[0034] The PMMA layer comprises the following components: PMMA resin, impact modifier and antioxidant, wherein the weight ratio of the PMMA resin, impact modifier and antioxidant is (70-85): (5-13): (0.1-0.4);

[0035] The impact modifier comprises the following components in parts by weight: 15-20 parts of n-butyl acrylate, 15-20 parts of methyl methacrylate, 5-8 parts of styrene, 0.8-1.2 parts of initiator, 0.5-1 parts of grafting agent, 0.5-1 parts of crosslinking agent, 1-2 parts of emulsifier, 0.1-0.3 parts of magnesium sulfate and 70-80 parts of water;

[0036] The PC layer comprises the following components: PC resin and nanoparticles, and the weight ratio of the PC resin to the nanoparticles is (20-30): (2-4).

[0037] The PC-PMMA composite protective film of the present application is prepared by the following method, comprising the following steps:

[0038] S1, taking PMMA resin, impact modifier and antioxidant to prepare PMMA particles, taking PC resin and nanoparticles to prepare PC particles;

[0039] S2, melting the PMMA particles, and extruding at 245-255° C. to obtain a PMMA melt; melting the PC particles, and extruding at 260-270° C. to obtain a PC melt;

[0040] S3, distributing the PMMA melt and the PC melt into a die head for double-layer composite co-extrusion, plasticization, calendering, pulling, cooling and shaping, to obtain a PC-PMMA composite protective film.

[0041] The present application modifies the surface of nano-silica and nano-zirconium dioxide with a layer of polydopamine. The surface functionalization of polydopamine improves the dispersibility of nano-silica, nano-zirconium dioxide and titanium dioxide in PC resin, strengthens the bonding strength between nano-silica, nano-zirconium dioxide and PC resin, and can effectively improve the wear resistance and scratch resistance of the PC layer. At the same time, polydopamine is an adhesive biological adhesive. When nano-silica and nano-zirconium dioxide with surface modified with polydopamine are introduced into the PC layer, the adhesion between the PC layer and the PMMA layer can be enhanced through the adhesion of polydopamine, thereby enhancing the interaction between them, and then improving the toughness of the PC-PMMA composite protective film.

[0042] The present application realizes the formation and mutual connection of PC layer and PMMA layer by co-extrusion after PC melt and PMMA melt are separated into runners, and utilizes the high temperature during co-extrusion to improve the interfacial adhesion between PC layer and PMMA layer, thereby obtaining better mechanical properties, and the obtained PC-PMMA composite protective film has better comprehensive performance. Specific embodiments

[0044] The PMMA resin model is Evonik 8N;

[0045] PC resin was purchased from Teijin Co., Ltd. of Japan, brand L-1250Y;

[0046] Antioxidant DLTP: Changzhou Xince Polymer Materials Co., Ltd.

[0047] Nano-silicon dioxide, nano-zirconium dioxide: Nanjing Dongna Biotechnology Co., Ltd.;

[0048] n-Butyl acrylate, styrene, methyl methacrylate: Jinan Yuanxiang Chemical Co., Ltd.;

[0049] Maleic anhydride grafted polyolefin elastomer: Japan Mitsui Chemicals POE MH5040;

[0050] Dimethyl silicone oil emulsifier: Jiangsu Haian Petrochemical Plant;

[0051] Hexamethylene diisocyanate: CAS: 822-06-0, Aladdin;

[0052] Azobisisobutyronitrile: CAS: 78-67-1, Aladdin;

[0053] Tris(hydroxymethyl)aminomethane: Jiangsu Chuangteng New Material Technology Co., Ltd.;

[0054] Dopamine hydrochloride: Jiangxi Muzan Biotechnology Co., Ltd.

[0055] Preparation Example 1-3 Preparation of impact modifier

[0056] Preparation Example 1

[0057] The impact modifier is prepared by the following method: 1g of an emulsifier and 70g of water are mixed and heated to 75-78°C, 15g of n-butyl acrylate, 5g of styrene, 0.5g of a grafting agent and 0.5g of a cross-linking agent are added and stirred and mixed, 0.8g of an initiator and 15g of methyl methacrylate are added and stirred and mixed, 0.1g of magnesium sulfate is added, and then filtered and dried to obtain the impact modifier; the emulsifier is a dimethyl silicone oil emulsifier, the grafting agent is a maleic anhydride grafted polyolefin elastomer, the cross-linking agent is hexamethylene diisocyanate, and the initiator is azobisisobutyronitrile.

[0058] Preparation Example 2

[0059] The impact modifier is prepared by the following method: 1.5g of emulsifier and 75g of water are mixed and heated to 76°C, 7g of n-butyl acrylate, 6g of styrene, 0.8g of grafting agent and 0.7g of cross-linking agent are added and stirred and mixed, 1g of initiator and 17g of methyl methacrylate are added and stirred and mixed, 0.2g of magnesium sulfate is added, and then filtered and dried to obtain the impact modifier.

[0060] Preparation Example 3

[0061] The impact modifier is prepared by the following method: 2g of emulsifier and 80g of water are mixed and heated to 78°C, 20g of n-butyl acrylate, 8g of styrene, 1g of grafting agent and 1g of cross-linking agent are added and stirred and mixed, 1.2g of initiator and 20g of methyl methacrylate are added and stirred and mixed, 0.3g of magnesium sulfate is added, and then filtered and dried to obtain the impact modifier.

[0062] The specific dosage of the components of the impact modifiers of Preparation Examples 1-3 is shown in Table 1.

[0063] Table 1

[0064]

[0065] Example 1

[0066] A PC-PMMA composite protective film, comprising a PMMA layer and a PC layer;

[0067] The PMMA layer comprises the following components: 70 g of PMMA resin, 5 g of the impact modifier of Preparation Example 1, and 0.1 g of an antioxidant; the PC layer comprises the following components in parts by weight: 20 g of PC resin and 2 g of nanoparticles;

[0068] The antioxidant is antioxidant DLTP, and the nanoparticles are modified nano-silicon dioxide.

[0069] The preparation method of modified nano-silica is as follows: disperse 2g of nano-silica in 1L of deionized water, add 1.21g of tris(hydroxymethyl)aminomethane), adjust the pH of the solution to 8, and finally add 0.4g of dopamine hydrochloride. After stirring for 3-4h, filter, wash with deionized water and dry to obtain modified nano-silica.

[0070] A method for preparing a PC-PMMA composite protective film comprises the following steps:

[0071] S1, preparing PMMA particles: PMMA resin, impact modifier and antioxidant are mixed evenly to form a first mixture; the first mixture is put into a co-rotating kneading twin-screw extruder for blending and extrusion granulation, and the extrusion temperature is 220° C.; the extruded particles are dried at 80° C. for 4 hours to obtain the PMMA particles;

[0072] Preparation of PC particles: PC resin and nanoparticles are mixed uniformly to form a second mixture; the second mixture is put into a co-rotating kneading twin-screw extruder for blending and extrusion granulation, and the extrusion temperature is 260° C.; the extruded particles are dried at 120° C. for 4 hours to obtain the PC particles;

[0073] S2, melting the PMMA particles, and extruding at 250° C. to obtain a PMMA melt; melting the PC particles, and extruding at 260° C. to obtain a PC melt;

[0074] S3. The PMMA melt and the PC melt are distributed to the die head for double-layer composite co-extrusion, plasticization, calendering, pulling, cooling and shaping to obtain a PC-PMMA composite protective film with a thickness of 600 μm, a PMMA layer thickness of 40 μm, and a PC layer thickness of 560 μm.

[0075] Example 2-3

[0076] The difference between Example 2-3 and Example 1 is that the amounts of components of the PMMA layer and the PC layer are different. See Table 2 for the differences.

[0077] Table 2

[0078]

[0079] Comparative Example 1

[0080] The difference between Comparative Example 1 and Example 2 is that no impact modifier is added to the PMMA layer.

[0081] Comparative Example 2

[0082] The difference between Comparative Example 2 and Example 2 is that no nanoparticles are added to the PC layer.

[0083] Comparative Example 3

[0084] The difference between Comparative Example 3 and Example 2 is that no impact modifier is added to the PMMA layer, and no nanoparticles are added to the PC layer.

[0085] Example 4

[0086] The difference between Example 4 and Example 2 is that the impact modifier is the impact modifier prepared in Preparation Example 2.

[0087] Example 5

[0088] The difference between Example 5 and Example 2 is that the impact modifier is the impact modifier prepared in Preparation Example 3.

[0089] Example 6

[0090] The difference between Example 6 and Example 4 is that the nanoparticles are modified nano zirconium dioxide.

[0091] The preparation method of modified nano zirconium dioxide is as follows: disperse 2g of nano zirconium dioxide in 1L of deionized water, add 1.21g of tris(hydroxymethyl)aminomethane, adjust the pH of the solution to 8, and finally add 2g of dopamine hydrochloride. After stirring for 3-4h, filter, wash with deionized water and dry to obtain modified nano zirconium dioxide.

[0092] Example 7

[0093] The difference between Example 7 and Example 4 is that the nanoparticles are modified nano-silicon dioxide and modified nano-zirconium dioxide in a weight ratio of 2:1.

[0094] Example 8

[0095] The difference between Example 8 and Example 4 is that the nanoparticles are modified nano-silicon dioxide and modified nano-zirconium dioxide in a weight ratio of 3:1.

[0096] Example 9

[0097] The difference between Example 9 and Example 4 is that the nanoparticles are modified nano-silicon dioxide and modified nano-zirconium dioxide in a weight ratio of 4:1.

[0098] Example 10

[0099] The difference between Example 10 and Example 4 is that the nanoparticles are nano-silicon dioxide.

[0100] Experimental detection bending test: The XHS-ZW-200 bending machine was used to perform a bending test on the PC-PMMA composite protective film. The longitudinal bending was 170°, and the bending rate was 9° per second. The longitudinal bending refers to the two ends of the composite protective film along the calendering direction, one end is fixed and the other end is bent. The composite protective film is observed for cracking and breaking. The bending conditions with cracking and breaking as the damage levels increase progressively are recorded and counted. The bending angles of the composite protective film with the highest damage level are recorded and counted. The bending toughness of the cracked composite protective film is better than that of the broken composite protective film, and the larger the cracking or breaking angle, the better the bending toughness. The test results are shown in Table 3.

[0101] Impact strength test: 10 sheets of the prepared PC-PMMA composite protective films were taken from Examples 1-10 of the present application and Comparative Examples 1-3, and the composite protective films were placed in a -20°C environment and frozen for 4 hours. After being taken out, the four corners of the composite protective films were fixed, and a 110 g steel ball was freely dropped from a height of 130 cm from the composite protective film to impact the PMMA layer to observe whether cracks appeared. The test results are shown in Table 3.

[0102] Test results

[0103] Table 3

[0104]

[0105]

[0106] Results Analysis

[0107] Combining Examples 1-3 and Comparative Examples 1-3 and Table 3, it can be seen that the PC-PMMA composite protective film prepared according to the raw material components and ratios of the present application has good bending toughness, high impact strength, and good comprehensive mechanical properties. The impact modifier added to the PMMA layer can effectively enhance the impact strength of the PC-PMMA composite protective film, and the modified nanoparticles added to the PC layer can effectively improve the toughness of the PC-PMMA composite protective film.

[0108] In combination with Examples 4-10, Example 2 and Table 3, it can be seen that the modified nano-silica selected in the present application can improve the toughness of the PC-PMMA composite protective film more than the unmodified nano-silica; when the modified nano-silica and the modified nano-zirconium dioxide are compounded, and the weight ratio of the modified nano-silica to the modified nano-zirconium dioxide is (2-4):1, the toughness of the obtained PC-PMMA composite protective film is better.

[0109] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A PC-PMMA composite protective film, characterized in that: Including PMMA layer and PC layer; The PMMA layer comprises the following components: PMMA resin, impact modifier and antioxidant, wherein the weight ratio of the PMMA resin, impact modifier and antioxidant is (70-85): (5-13): (0.1-0.4); The impact modifier comprises the following components in parts by weight: 15-20 parts of n-butyl acrylate, 15-20 parts of methyl methacrylate, 5-8 parts of styrene, 0.8-1.2 parts of initiator, 0.5-1 parts of grafting agent, 0.5-1 parts of crosslinking agent, 1-2 parts of emulsifier, 0.1-0.3 parts of magnesium sulfate and 70-80 parts of water; The PC layer comprises the following components: PC resin and nanoparticles, wherein the weight ratio of the PC resin to the nanoparticles is (20-30): (2-4); The nanoparticles are modified nanoparticles, and the modified nanoparticles are modified nano-silicon dioxide and modified nano-zirconium dioxide. The weight ratio of the modified nano-silicon dioxide to the modified nano-zirconium dioxide is (2-4):

1.

2. The PC-PMMA composite protective film according to claim 1, characterized in that: The impact modifier is prepared by the following method: mixing an emulsifier and water and heating to 75-78° C., adding n-butyl acrylate, styrene, a grafting agent and a crosslinking agent, stirring and mixing, then adding an initiator and methyl methacrylate, stirring and mixing, then adding magnesium sulfate, and then filtering and drying to obtain the impact modifier.

3. The PC-PMMA composite protective film according to claim 1, characterized in that: The preparation method of the modified nanoparticles is as follows: unmodified nanoparticles are dispersed in deionized water, tris(hydroxymethyl)aminomethane) is added, and finally dopamine hydrochloride is added, stirred for reaction for 3-4 hours, filtered, washed with deionized water, and then dried to obtain modified nanoparticles.

4. The PC-PMMA composite protective film according to claim 3, characterized in that: The weight ratio of the unmodified nanoparticles, tris(hydroxymethyl)aminomethane) and dopamine hydrochloride is (2-4):(1-2):(0.3-0.5).

5. The PC-PMMA composite protective film according to claim 1, characterized in that: The thickness ratio of the PMMA layer to the PC layer is 1:(12-16), and the thickness of the PC-PMMA composite protective film is 450-600 μm.

6. A method for preparing the PC-PMMA composite protective film according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, taking PMMA resin, impact modifier and antioxidant to prepare PMMA particles, taking PC resin and nanoparticles to prepare PC particles; S2, melting the PMMA particles, and extruding at 245-255° C. to obtain a PMMA melt; melting the PC particles, and extruding at 260-270° C. to obtain a PC melt; S3, distributing the PMMA melt and the PC melt into a die head for double-layer composite co-extrusion, plasticization, calendering, pulling, cooling and shaping, to obtain a PC-PMMA composite protective film.

7. The method for preparing the PC-PMMA composite protective film according to claim 6, characterized in that: The preparation method of the PMMA particles is as follows: PMMA resin, impact modifier and antioxidant are mixed evenly to form a first mixture; the first mixture is blended and extruded into granules at an extrusion temperature of 210-230° C.; the extruded particles are dried at 75-85° C. for 3.5-5 hours to obtain the PMMA particles.

8. The method for preparing the PC-PMMA composite protective film according to claim 6, characterized in that: The preparation method of the PC particles is: mixing PC resin and nanoparticles uniformly to form a second mixture; extruding the second mixture into granules at an extrusion temperature of 250-270° C.; and drying the extruded particles at 110-130° C. for 3.5-5 hours to obtain the PC particles.

Citation Information

Patent Citations

  • Rubber-plastic alloy material with excellent oil and corrosion resistance, and preparation method thereof

    CN111040410A

  • Two-layer co-extruded high-wear-resistance flame-retardant PC / PMMA composite sheet and preparation method thereof

    CN113999413A

  • Heat-resistant toughened PMMA (polymethyl methacrylate) film and preparation method thereof

    CN117445507A